2019
DOI: 10.3390/cancers11111659
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Tumor Cells in Pancreatic Cancer: Current Perspectives

Abstract: Pancreatic cancer is the fourth leading cause of cancer-related death in the USA and Europe; early symptoms and screenings are lacking, and it is usually diagnosed late with a poor prognosis. Circulating tumor cells (CTCs) have been promising new biomarkers in solid tumors. In the last twenty years (1999–2019), 140 articles have contained the key words “Circulating tumor cells, pancreatic cancer, prognosis and diagnosis.” Articles were evaluated for the use of CTCs as prognostic markers and their correlation t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
72
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(74 citation statements)
references
References 75 publications
2
72
0
Order By: Relevance
“…The disseminated tumor cells (DTCs) and circulating tumor cells (CTCs) have been detected in the peripheral blood of many cancer types, including colorectal cancer [58], breast cancer [59], hepatocellular cancer [60] and pancreatic cancer [61][62][63]. The DTCs and CTCs in the blood could be awakened after surgery, initiating metastasis [64].…”
Section: Discussionmentioning
confidence: 99%
“…The disseminated tumor cells (DTCs) and circulating tumor cells (CTCs) have been detected in the peripheral blood of many cancer types, including colorectal cancer [58], breast cancer [59], hepatocellular cancer [60] and pancreatic cancer [61][62][63]. The DTCs and CTCs in the blood could be awakened after surgery, initiating metastasis [64].…”
Section: Discussionmentioning
confidence: 99%
“…Circulating tumor cells (CTCs) have been evaluated as diagnostic and survival prognostic markers in patients with PDAC [ 73 ]. Peripheral CTCs represent cells originating from the primary lesion that may be undetectable by imaging tests and non-accessible to biopsy with imaging guidance [ 74 ].…”
Section: Biomarkersmentioning
confidence: 99%
“…With the ability to enter the peripheral circulatory system, circulatory tumor cells (CTC) vary in individual and express both epithelial and mesenchymal markers [79]. It has been reported that such cells can be detected in the peripheral blood of 40% ~ 100% of pancreatic cancer patients, which may be used for the early diagnosis of pancreatic cancer [80].…”
Section: Serological Markmentioning
confidence: 99%